2023
DOI: 10.1200/jco.2023.41.16_suppl.e13607
|View full text |Cite
|
Sign up to set email alerts
|

Primary care provider perceptions of patient participation in a multi-cancer early detection trial.

Abstract: e13607 Background: Randomized clinical trials of multi-cancer early detection (MCED) tests are being planned, and primary care providers (PCPs) are likely to encounter patients who are considering participation. Little information has been reported about provider support for patient participation in such trials. Methods: We surveyed PCPs from 4 practices in a large health system to learn about their views on patient participation in a hypothetical MCED test trial. The PCPs received a link to view a patient-or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
2
0
0
Order By: Relevance
“…Overall, study findings indicate that primary care patients may be receptive to MCED trial participation. In another study, our research team found a high level of support for patient participation in such trials among primary care providers 54 . As suggested earlier, findings reported here suggest efforts to recruit primary care patients to MCED trials may be successful, especially when patient education and decision counseling are integrated into an EMR‐based strategy for identifying eligible patients 55,56 …”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Overall, study findings indicate that primary care patients may be receptive to MCED trial participation. In another study, our research team found a high level of support for patient participation in such trials among primary care providers 54 . As suggested earlier, findings reported here suggest efforts to recruit primary care patients to MCED trials may be successful, especially when patient education and decision counseling are integrated into an EMR‐based strategy for identifying eligible patients 55,56 …”
Section: Discussionsupporting
confidence: 71%
“…In another study, our research team found a high level of support for patient participation in such trials among primary care providers. 54 As suggested earlier, findings reported here suggest efforts to recruit primary care patients to MCED trials may be successful, especially when patient education and decision counseling are integrated into an EMR-based strategy for identifying eligible patients. 55,56 Nonetheless, it is important to mention that we asked patients to consider joining a "planned" MCED trial, rather than an ongoing MCED trial that was open at the time of contact.…”
Section: 813supporting
confidence: 62%